2003
DOI: 10.1111/j.1151-2916.2003.tb03299.x
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of Glass by a Piezoelectric Secondary Phase

Abstract: A toughening concept for glass, based on exploiting the ferroelastic effect of piezoelectric particles embedded in a glass matrix, is described. It is hypothesized that the domains within a piezoelectric phase will align themselves in the direction of the stress field around an advancing crack, thus absorbing energy and contributing to toughening. A powder technology route was optimized to fabricate lead‐containing glass‐matrix composites with up to 30 wt% of a lead zirconate titanate (PZT) particulate phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…14 The complexity of the recycling of CRT glasses may be successfully solved by a sintering approach. It has been already demonstrated the feasibility of innovative glass-based products, like glass matrix composites, [15][16][17][18][19] and glass foams, 20,21 by a simple and cost-effective powder technology route. The fundamental remark of such approach is that CRT glasses possess a relatively low softening temperature, which is particularly profitable in viscous flow sintering, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…14 The complexity of the recycling of CRT glasses may be successfully solved by a sintering approach. It has been already demonstrated the feasibility of innovative glass-based products, like glass matrix composites, [15][16][17][18][19] and glass foams, 20,21 by a simple and cost-effective powder technology route. The fundamental remark of such approach is that CRT glasses possess a relatively low softening temperature, which is particularly profitable in viscous flow sintering, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental remark of such research is that CRT glasses possess a relatively low softening temperature, which could be particularly profitable in viscous flow sintering applications. Glass foams 14,15 and glass matrix composites [16][17][18][19] were successfully fabricated from CRT glasses. In the specific field of glass-matrix composites it has been shown that CRT glasses are suitable for the obtainment of highly dense composites in spite of cold pressing and pressure-less sintering (it is well known that the densest glass-matrix composites are developed by hot pressing).…”
Section: Introductionmentioning
confidence: 99%
“…(2) When a crack expands to a LiNbO 3 grain, the piezoelectric LiNbO 3 will transform part of the fracture energy into electrical energy, and domain movement may be induced in the LiNbO 3 grain to further dissipate the fracture energy. Such a process is called ''piezoelectric energy dissipation toughening mechanism'' [3][4][5][6][7][8][9][10][11]. (3) LiNbO 3 partially reacts with HAp to form CaNb 2 O 6 , which belongs to central symmetric point groups, and possesses no piezoelectric effect.…”
Section: Density and Mechanical Propertiesmentioning
confidence: 99%
“…When a crack propagates in the composite, a part of fracture energy, will be transformed into electrical energy or dissipated by a stress-induced domain movement, leading to an enhanced fracture resistance [3,4]. This approach has been successfully applied in various composite systems: Nd 2 Ti 2 O 7 /Al 2 O 3 [4], BaTiO 3 /3Y-TZP [5], Sr 2 Nb 2 O 7 /3Y-TZP [6], Nd 2 Ti 2 O 7 /8Y-FSZ [7], LiTaO 3 / Al 2 O 3 [8], BaTiO 3 /MgO [9], BaTiO 3 /La 2 Zr 2 O 7 [10], and PZT/glass [11]. As compared with traditional toughening methods, the piezoelectric toughening method not only can enhance the mechanical properties, but also introduces novel electrical properties into the toughened ceramics.…”
Section: Introductionmentioning
confidence: 99%